Factors that influence interest in purchasing Scarlett Whitening products among Solo Raya women - Aoliya Herman; Putri Maisara (Universitas Pendidikan Nasional, 2023)
This research was conducted on women who lived in Solo Raya and was useful for looking separately at the influence of the variable factors: celebrity endorser, product quality, and brand image on interest in purchasing Scarlett Whitening products using a quantitative approach method. Data sources used literature studies and the distribution of questionnaires that had been processed to provide valid results. The population in this research was Solo Raya women who knew the Scarlett Whitening product. The sample used the Roscoe formula and obtained a total of 147 respondents by setting special criteria (purposive sampling). The results of the partial explanation in testing multiple linear regression analysis and the t-test in this research showed that the variables celebrity endorser, product quality, and brand image had positive and significant influence values, so they could have a good impact on interest in purchasing Scarlett Whitening products. With the findings from the help of celebrity endorsers to review products, product quality, and the good brand image of Scarlett Whitening, it could make women more interested, and the variable factors that had been focused on in this research could increase buying interest in Scarlett Whitening products.